When Charley Met granpa - Hest, Amy and Oxenbury, Helen (London Walker Books, 2013)
"Dear Grandpa ... When are you coming to see Charley? Bring a big suitcase and stay a long time and I'll meet you at the station ..." Readers fell in love with Henry and his truly adorable new puppy, Charley, in Charley's First Night. In this beautiful follow-up title, Henry hopes - very much - that his Grandpa, who is coming for a visit, will love Charley just as much as he does (a LOT). But Grandpa is a little wary of dogs ... he's never been friends with one before. Luckily, Charley isn't any ordinary little puppy, he's a very smart one and this could be the beginning of a very beautiful friendship indeed
Include Color Illustrations
Keywords: Puppies -- Grandparent and child -- Children's stories